Pengembangan Inventori Stres Akademik Siswa Sekolah Menengah Pertama (SMP) Negeri Kota Malang - Imamah Yulinawati; Khairul Bariyyah; Devi Permatasari (Universitas Kanjuruhan Malang, 2018)
This development research aims to produce an academic stress scale to measure the stress level of students who have high validity and reliability. So that it can facilitate counselors in helping students with academic stress problems. This development research uses a method or strategy developed by Borg and Gall involving 300 students. The sample of this study were junior high school students aged 13-16 years who were selected with cluster random sampling technique, Pearson Product Moment data analysis, Cronbach Alpha, normality test and factor analysis. This development research resulted in academic stress instruments consisting of 31 valid items and 15 correlating factors. So that the final results of this academic stress inventory can be used to measure students' academic stress levels.